Non-comorbid Respiratory Factor and Work of Breathing in Pediatric COVID-19 Patient: How is Their Synergistic Correlation with the Level of Care? - Defi Efendi; Maria Dyah Kurniasari; Mega Hasanul Huda; Raudha Ilmi Farid; Yohanes Andy Rias; Yogi Prawira; Nina Dwi Putri; Ayuni Rizka Utami; Titik Ambar Asmarini; Pande Lilik Lestari; Pricilia Mais; Abram Babakal (Nurse Media Journal of Nursing, 2022)
Background: Work of breathing (WOB) and non-comorbidities factors in the respiratory system are the two probable findings in pediatric COVID-19 patients. However, the association of those factors with level of care was not well reported.Purpose: This study aimed to identify the relation between potential predictors including comorbidity, low nutritional fulfillment, infectious disease, shock, cough, O2 saturation reduction, abnormal blood gas analysis and sore throat with the level of care among pediatric COVID-19 patients. We also analyzed the synergistic correlation of non-comorbidities factors in the respiratory system and work of breathing to predict level of care in pediatric COVID-19 patients.Methods: A cross-sectional study was conducted in the six referral hospitals from July to September 2020 in four provinces in Indonesia. An observation checklist was used to collect data from the medical records of pediatric patients with COVID-19, including medical diagnosis, demographic, and clinical manifestation. This study included 423 participants aged from 0 to 18. The multivariate logistic regression was performed to test the adjusted odds ratios (AORs) with the 95% confidence intervals (CIs) of the association between WOB, non-comorbid respiratory, and level of care. Moreover, dummy variables (2x2) were made to analyze synergistic correlation of non-comorbid respiratory disease and WOB. The AOR with the 95% CIs was applied in the association between the complication of non-comorbid respiratory diseases and high work of breathing with level of care among pediatric patients with COVID-19.Results: Results showed that age, presence of comorbidity, nutritional fulfillment, infectious disease, shock, work of breathing, O2 saturation reduction, abnormal blood gas analysis, sore throat, and convulsive meningeal consciousness were significantly associated with the level of care (p<0.05). Pediatric patients with non-comorbid respiratory and increased work of breathing had a 15.59 times higher risk of requiring PICU care level (p<0.01). Meanwhile, pediatric patients who experienced both non-comorbid respiratory and increased work of breathing had a 5.76 times risk of requiring an intermediate level of care (p<0.05), and 9.32 times higher risk of requiring a PICU level of care (p<.05).Conclusion: It was found that both non-comorbid respiratory and increased WOB had a significant relationship with the level of care for pediatric patients with COVID-19. Nurse should take into account those clinical findings to increase the awareness in monitoring clinical deterioration in pediatric COVID-19 patients.